Lower extremity venous reflux - Baliyan, Vinit; Tajmir, Shahein; Hedgire, Sandeep S.; Ganguli, Suvranu; Prabhakar, Anand M. (Cardiovascular Diagnosis and Therapy; Vol 6, No 6 (December 29, 2016): Cardiovascular Diagnosis and Therapy (Advanced Venous Imaging and Image-guided Venous Interventions), 2016)
Venous incompetence in the lower extremity is a common clinical problem. Basic understanding of venous anatomy, pathophysiologic mechanisms of venous reflux is essential for choosing the appropriate treatment strategy. The complex interplay of venous pressure, abdominal pressure, venous valvular function and gravitational force determine the venous incompetence. This review is intended to provide a succinct review of the pathophysiology of venous incompetence and the current role of imaging in its management.